The Degree of Mutual Anisotropy of Biological Liquid Crystals Net during the Diagnostics of Human Tissues Birefringence. (16th May 2010) - Angelsky, Oleg V.; Ushenko, Yuriy A.
Abstract : To characterize the degree of consistency of parameters of the optically uniaxial birefringent liquid crystals (protein fibrils) nets of biological tissues a new parameter-complex degree of mutual anisotropy is suggested. The technique of polarization measuring the coordinate distributions of the complex degree of mutual anisotropy of biological tissues is developed. It is shown that statistic approach to the analysis of complex degree of mutual anisotropy distributions of biological tissues of various morphological and physiological states and optical thicknesses appears to be more sensitive and efficient in differentiation of physiological state in comparison with investigations of complex degree of mutual polarization of the corresponding laser images.